Outbreak Preparedness and Response Strategies in ASEAN Member states - A Scoping Review - Fingani Annie Mphande-Nyasulu; Nan Jiun Yap; Chin Hai Teo; Li-Yen Chang; Sun Tee Tay (My University, 2024)
The 21
Keywords: Preparedness; Emergency Response; Crisis Response; Disaster Response; Agricultural risk and resilience